Early and Unusual Restenosis Following Carotid Endarterectomy for Symptomatic Carotid Web: A Case Report - Haruki Hoshikawa; Yasuhisa Akaiwa; Yoshiyuki Matsumoto; Issei Takano; Kensuke Suzuki; Kohei Miyagawa; Toshiki Nakamura; Mari Tada; Tomoyuki Miyamoto (Neurology and Clinical Neuroscience, 2026)
ABSTRACT A 52‐year‐old man presented with acute motor aphasia. Brain MRI revealed embolic infarctions in the left middle cerebral artery territory. CT angiography and carotid ultrasonography demonstrated a shelf‐like projection arising from the posterior wall of the left carotid bulb, consistent with a carotid web (CW). Transcranial Doppler ultrasonography detected microembolic signals, supporting the diagnosis of artery‐to‐artery embolism associated with the CW. Carotid endarterectomy (CEA) was performed to prevent recurrent ischemic events. Histopathological examination revealed intimal‐type fibromuscular dysplasia with focal atheromatous changes. Approximately 6 months after surgery, significant restenosis developed at the surgical site, accompanied by reduced ipsilateral cerebral blood flow. Carotid artery stenting was subsequently performed, resulting in stabilization without recurrent ischemic events. CW may act not only as an embolic source but also as a proliferative arterial wall lesion. Careful postoperative surveillance is warranted because early restenosis may occur following CEA.